Kitab kuning: Jembatan menuju pemahaman Islam yang mendalam di Pesantren Salafiyah Bangil - Rohmah, Maftuhatur (Maliki Interdisciplinary Journal, 2024)
Salafiyah Bangil Islamic Boarding School, East Java, is known as one of the oldest and most respected Islamic educational institutions in Indonesia. In this pesantren, the Kitab Kuning is the main pillar in the learning process, leading the santri to a deep and comprehensive understanding of Islam. This article explores the central role of the Kitab Kuning at Salafiyah Bangil Islamic Boarding School. Beginning with an explanation of the history and tradition of learning the Kitab Kuning in pesantren, the article then explores the teaching methods applied, including sorogan and bandongan. Furthermore, the article discusses the various disciplines studied through the Kitab Kuning, such as fiqh, usuluddin, Qur'anic exegesis, and hadith science. Emphasis is placed on how the Kitab Kuning not only transfers religious knowledge but also instills moral values and spirituality in the santri. In conclusion, this article highlights the Kitab Kuning as a solid bridge for santri in Salafiyah Bangil Pesantren to achieve a deep and comprehensive understanding of Islam. The tradition of learning Kitab Kuning in this pesantren is clear evidence of the pesantren's commitment to preserving the intellectual treasures of Islam and giving birth to a generation of Muslims who are knowledgeable and have noble character.